2000
DOI: 10.1212/wnl.55.2.294
|View full text |Cite
|
Sign up to set email alerts
|

Striatal serotonin is depleted in brain of a human MDMA (Ecstasy) user

Abstract: The authors found that striatal levels of serotonin and those of its metabolite 5-hydroxyindoleacetic acid were severely depleted by 50 to 80% in brain of a chronic user of methylenedioxymethamphetamine (MDMA) whereas concentrations of dopamine were within the normal control range. Our data suggest that MDMA exposure in the human can cause decreased tissue stores of serotonin and therefore some of the behavioral effects of this drug of abuse could be caused by massive release and depletion of brain serotonin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(62 citation statements)
references
References 6 publications
3
57
0
2
Order By: Relevance
“…MDMA has acute and longterm effects on 5-HT in several species including several non-human primates (baboons, marmosets, squirrel, rhesus, and cynomologous monkeys), pigeons, rabbits, guinea-pigs, rats, and some mouse strains [58,100,113,130,145]. Recent investigations have begun to determine that humans may exhibit similar alterations in 5-HT and serotonergic mediated function due to repeated ecstasy use [61,66,72,113]. As ecstasy is typically used recreationally with other substances, researchers have begun to determine how MDMA interacts with alcohol [21], caffeine [95], LSD [137], marijuana [107] and methamphetamine [24][25][26] in adults.…”
Section: Historymentioning
confidence: 99%
“…MDMA has acute and longterm effects on 5-HT in several species including several non-human primates (baboons, marmosets, squirrel, rhesus, and cynomologous monkeys), pigeons, rabbits, guinea-pigs, rats, and some mouse strains [58,100,113,130,145]. Recent investigations have begun to determine that humans may exhibit similar alterations in 5-HT and serotonergic mediated function due to repeated ecstasy use [61,66,72,113]. As ecstasy is typically used recreationally with other substances, researchers have begun to determine how MDMA interacts with alcohol [21], caffeine [95], LSD [137], marijuana [107] and methamphetamine [24][25][26] in adults.…”
Section: Historymentioning
confidence: 99%
“…The popularity of this drug has given rise to concern, since preclinical research has demonstrated that repeated doses of MDMA can cause serotonergic neurodegeneration in animals (eg Ricaurte et al, 1992Ricaurte et al, , 2000Steele et al, 1994;Green et al, 1995), and there is some evidence that chronic consumption of ecstasy is associated with protracted dysregulation of 5-HT systems in humans. Drug-free ecstasy users have been found to have low levels of 5-HT, and its metabolite 5-HIAA Kish et al, 2000). Additionally, neuroimaging studies suggest that extensive exposure to ecstasy may deplete 5-HT in humans (eg McCann et al, 1998;Semple et al, 1999;Reneman et al, 2000), although such effects appear to recover after prolonged abstinence (Reneman et al, 2001; Thomasius et al, 2003;Buchert et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, at the time of this writing, there exist no published reports describing frank cell loss, argyrophilia, or reactive gliosis in postmortem human brain tissue from MDMA users. As such, some researchers have relied instead on more ambiguous measures of axon terminal integrity in human MDMA users, such as depletion of serotonin (5-HT) content (see, e.g., Kish et al 2000), reduced binding to plasmalemmal 5-HT transporters (see, e.g., McCann et al 1998McCann et al , 2005Semple et al 1999), or compensatory upregulation of postsynaptic 5-HT receptors (see, e.g., Reneman et al 2002). Other researchers have eschewed the study of human drug users in favor of animal models, which frequently involved the application of various interspecies dose scaling procedures.…”
Section: Introductionmentioning
confidence: 99%